Otolith Growth Pattern of Puntius Schwanenfeldii from the Koto Panjang Reservoir, Regency of Kampar, Riau, Indonesia - Eni Sumiarsih; Kamaruddin Eddiwan (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
Koto Panjang Reservoir is the largest reservoir in Riau Province, there are many efforts of floating net cage (KJA) by using feed (pellet) continuously. As a result of many feeds that settle in the bottom of the waters because it is not consumed by the fish. The purpose of this research is to know the pattern of growth circle otolith of kapiek fish that live around KJA and in waters that there is no KJA (natural). The study was conducted from March to September 2016. This study used survey method, with 5 stations, where St1 and St 2 were in waters without KJA, while St3, St4 and St5 were in the waters around KJA.